2017
DOI: 10.1371/journal.pone.0170660
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Experience of Chinese Calligraphic Handwriting Is Associated with Better Executive Functions and Stronger Resting-State Functional Connectivity in Related Brain Regions

Abstract: Chinese calligraphic handwriting (CCH) is a traditional art form that requires high levels of concentration and motor control. Previous research has linked short-term training in CCH to improvements in attention and memory. Little is known about the potential impacts of long-term CCH practice on a broader array of executive functions and their potential neural substrates. In this cross-sectional study, we recruited 36 practitioners with at least 5 years of CCH experience and 50 control subjects with no more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…The significant results of this finger writing therapy for brain stroke rehabilitation are interpreted from the framework of sensorimotor feedback theory. 8 , 10 , 33 , 34 This is learned and practiced by the finger tracing on the groove of the carved Chinese character plates, using the tactile, 27 , 28 feeling, and the task tracking 29 , 30 of feedback control of the sensorimotor movement of the writing finger in order to stimulate brain responses and activation 14 to elicit neuroplasticity. 22 , 33 – 36 This dynamic practice contributes to the effectiveness of the stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant results of this finger writing therapy for brain stroke rehabilitation are interpreted from the framework of sensorimotor feedback theory. 8 , 10 , 33 , 34 This is learned and practiced by the finger tracing on the groove of the carved Chinese character plates, using the tactile, 27 , 28 feeling, and the task tracking 29 , 30 of feedback control of the sensorimotor movement of the writing finger in order to stimulate brain responses and activation 14 to elicit neuroplasticity. 22 , 33 – 36 This dynamic practice contributes to the effectiveness of the stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging research has focused on CCH and brain activation studies. 14 Valid resting-state fMRI data were collected from the CCH and control participants. The CCH individuals showed better neural functions of updating and inhibition, but the two groups did not differ in shifting.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous research that found both structural and functional brain plasticity in response to many types of intensive training such as musical training [3, 4], driving [5], and juggling [6, 7], we have examined brain plasticity related to CCH training. Our previous two studies found that CCH training strengthened the RSFC of brain areas involved in updating and inhibition [8] and decreased the volume of the posterior cingulate cortex (PCC) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Given our previous findings of CCH training’s effects on the RSFC of certain brain areas [8], we hypothesized long-term CCH practicing would have an effect on the topological parameters of the resting-state brain network, including the frontal and parietal cortices, basal ganglia, and PCC. We explored the long-term CCH training’s effect on the topological characteristics of the whole brain and four specific modules.…”
Section: Introductionmentioning
confidence: 99%
“…The CCH group also shows stronger resting-state functional connectivity than the control group in the brain areas involved in updating and inhibition. These outcomes suggest that long-term CCH training may be associated with improvements in specific aspects of the executive functions and the strengthened neural networks in related brain regions (Chen et al, 2017). At a deeper level of analysis, when processing the visual-spatial configurations of Chinese characters at the cortical level, the act of writing can initiate and facilitate cognitive activities and functions of related cortical substrates (Kao et al, 2018;Xu, Kao, Zhang, Lam, & Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%